Floral response to the Late Triassic Carnian Pluvial Episode - Zhang, Peixin; Yang, Minfang; Lu, Jing; Jiang, Zhongfeng; Zhou, Kai; Xu, Xiaotao; Wang, Ye; Wu, Li; Chen, Huijuan; Zhu, Xuran; Guo, Yanghang; Ye, Huajun; et al. (Frontiers in Ecology and Evolution, 2023)
The Late Triassic Carnian Pluvial Episode (CPE; ca. 234–232 Ma) was characterized by dramatic global temperature and humidity increases, which in many terrestrial settings was accompanied by changes from arid to humid vegetation types. This study reviews current evidence of terrestrial floral composition and distribution during the CPE and analyzes spatial and temporal variation with relation to potential environmental driving mechanisms. Available evidence suggests the CPE was a globally significant event that triggered significant increases in the abundance of ferns and hygrophytes in terrestrial floras and freshwater algae in fluvial and lacustrine settings. These changes ended a long interval of relatively arid terrestrial climatic conditions since the Early Triassic and are linked temporally with eruptions of the oceanic plateau Wrangellia Large Igneous Province (LIP). The massive release of greenhouse gasses including isotopically light CO2 during 3–4 distinct pulses of Wrangellia volcanism appears to have been the main driver of CPE climate change. Each pulse enhanced global atmospheric circulation and the hydrological cycle and resulted in changes from arid to humid conditions that affected floral abundance and composition. Higher terrestrial primary productivity in humid phases facilitated increased burial of terrestrial organic carbon and led to the recommencement of peat accumulation, ending the coal gap that had persisted since the Earliest Triassic times. Enhanced movement of carbon from the atmosphere through the biosphere into the geosphere may have counteracted the warming effects of Wrangellia volcanic greenhouse gas emissions and ultimately led to the return of a steady climate state that terminated the warm and humid conditions of the CPE.